Analisis Kualitatif Kasus Gangren Pulpa Di Poliklinik Gigi Dalam Upaya Meningkatkan Kualitas Pelayanan Rumah Sakit Tk. IV Cijantung - Gama Bagus Kuntoadi; Rokiah Kusumapradja (MEDICORDHIF Jurnal Rekam Medis, 2018)
ABSTRACT “Rumah Sakit Tingkat IV Cijantung” is a type D hospital owned by Indonesian Armed Force (TNI-AD) which is located at 2nd Mahoni Street, Cijantung – Kesdam Jaya, East Jakarta, Indonesia. This hospital is equiped with 85 beds and also has several medical services unit such as an Emergency Unit, Polyclinic, Laboratory, Radiology, Pharmacy, and Operation Room. As a part of a Policlinic Unit, Dental Care Clinic have become a hospital frontline in interaction with their patients. By having a low medical services quality, it will affect on their patient satisfaction and then it will influence on their hospital revenue. There are so many ways to increase medical services quality, one of them is by doing a medical audit. As the result of this medical audit, the hospital manager will have an accurate data on certain level his medical unit services quality gained so far. Furthemore, this audit report will become a reference to determine their hospital policy to increasing hospital services quality. This research main purpose is to gain a medical quality services illustration on pulp gangrene case at hospital dental polyclinic. Research methodology which had been use is qualitative descriptive analysis by using checklist tool and then by interviewing all dental polyclinic staff at the hospital. The other result of this research is describing the existence of Medical Service Standard and Hospital Standard Operation Procedure (S.O.P) for pulp gangrene case, which will become their basic reference when treating their pulp gangrene patients. On the other hand, this research is also tried to describing dental polyclinic staff obstacles in providing pulp gangrene medical services to their patients. Keywords : medical record, medical audit, service quality, pulp gangrene